Formulating Social Media Blacklisting as An Additional Criminal Sanction for Online Child Sexual Crimes in Indonesia: A Normative and Comparative Analysis - Muhamad Adystia Sunggara; Zico Junius Fernando; Fardana Kusumah (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2026)
The expansion of social media is transforming the modus operandi of child sexual crimes by enabling offenders to groom, manipulate, exploit, and blackmail children through digital platforms. Indonesia’s current criminal justice system remained largely dependent on imprisonment and fines, while the offender’s post-conviction access to the same digital environment used to commit the crime was insufficiently regulated. Therefore, this study aimed to examine the possibility of formulating social media blacklisting as an additional criminal sanction for online child sexual crimes in Indonesia. A normative legal study was conducted with statutory, conceptual, and comparative methods to analyse Indonesian criminal law, child protection norms, digital rights, and comparative practices in the United Kingdom, the United States, South Korea, Germany, and Scandinavian jurisdictions. The results showed that social media blacklisting was normatively justified only when it was expressly regulated by statute, imposed by judicial decision, based on individual risk assessment, limited in duration and scope, and subject to proportionality review. This study contributed to penal reform scholarship by proposing a rights-based and risk-based model of digital additional punishment that protected children, prevented digital recidivism, and avoided unconstitutional blanket restrictions on access to information and expression.